Analisis Keterbatasan Kebijakan Pengelolaan Sampah Makanan di Jakarta: Pembelajaran dari Praktik Food Rescue FoodCycle Indonesia - Raynaldo Ghiffari Lubabah; Husnul Fitri; Renny Nurhasana (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Food waste is the largest contributor to municipal solid waste in Jakarta. Data from Indonesia's National Waste Management Information System (SIPSN) in 2023 indicate that food waste accounted for 49.87% of the city's total waste generation, equivalent to approximately 1,566,740 tons annually. Food waste management by the Jakarta Provincial Government has largely relied on a technocratic, end-of-pipe approach, while upstream prevention strategies, such as food rescue and food redistribution, have yet to be explicitly incorporated into local policies. This study aims to examine the limitations of Jakarta's current food waste management policies and to explore the role of community-based innovation through the food rescue and redistribution practices implemented by FoodCycle Indonesia as an alternative strategy for reducing urban food waste. A qualitative case study approach was employed, with data collected through in-depth interviews, field observations, document analysis, and a review of relevant policies issued by the Jakarta Provincial Government. The findings reveal that FoodCycle has developed a food rescue and redistribution model that remains outside the formal municipal waste management system. Its activities include rescuing edible surplus food, redistributing it to vulnerable communities, and fostering cross-sector collaboration among businesses, social organizations, and volunteers. Throughout 2024, FoodCycle rescued approximately 160 tons of edible surplus food, distributed it to 63,431 beneficiaries, and prevented an estimated 596,112 kg of CO2 emissions. These findings demonstrate that community-based food banking innovation not only contributes to reducing food waste but also has the potential to serve as a complementary governance model within Jakarta's urban food waste management system.